2019
DOI: 10.1186/s13765-019-0472-y
|View full text |Cite
|
Sign up to set email alerts
|

Natural occurrence of aflatoxins and ochratoxin A in meju and soybean paste produced in South Korea

Abstract: In this study, we investigated the occurrence of aflatoxins (AFs) and ochratoxin A (OTA) in meju and soybean paste produced in South Korea. Samples were collected from three regions divided on the basis of climate in South Korea. A total of 100 meju samples were analyzed over 3 years (2012-2015), and 45 soybean paste samples were analyzed in 2016. Mycotoxins were extracted with an immunoaffinity column method and quantified by high-performance liquid chromatography. AFs were detected in 10 of meju (10%) and 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 19 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…The excitation and emission wavelength for fluorescence detection used were 330 nm and 460 nm, respectively. OTA samples were analyzed using a reverse phase column C‐18 with 4.6 mm internal diameter, 250 mm column length, 3.5 μm particle size and isocratic mobile phase (acetonitrile, 57%; water, 41%, and acetic acid 2%) at a flow rate of 1 ml/min (Bauer & Gareis, 1987; Jeong et al, 2019). Calibration curve was constructed based on eight concentrations of standard OTA from Petromyces albertensis (Sigma‐Aldrich, Milwaukee, WI).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The excitation and emission wavelength for fluorescence detection used were 330 nm and 460 nm, respectively. OTA samples were analyzed using a reverse phase column C‐18 with 4.6 mm internal diameter, 250 mm column length, 3.5 μm particle size and isocratic mobile phase (acetonitrile, 57%; water, 41%, and acetic acid 2%) at a flow rate of 1 ml/min (Bauer & Gareis, 1987; Jeong et al, 2019). Calibration curve was constructed based on eight concentrations of standard OTA from Petromyces albertensis (Sigma‐Aldrich, Milwaukee, WI).…”
Section: Methodsmentioning
confidence: 99%
“…The slight fungal growth variations among the triplicate plates were considered by taking 1 ml of composite sample containing equal proportions of extracts from the triplicate plates for extraction of OTA. In order to purify the extracted OTA from the fungal cultures, samples were run through OTA immunoaffinity columns (VICAM, MA) (Jeong, Chung, & Hong, 2019). The procedures for purifying through immunoaffinity columns include briefly the addition of 1.5 ml of sample and 4 ml of phosphate buffered saline (PBS) solution into the column followed by a wash of the column with 5 ml of PBS at a flow rate of 1 ml/min.…”
Section: Methodsmentioning
confidence: 99%
“…Most of the AF contaminations were recorded in RYR from Malaysia ( n = 46/50) 33 , 34 and Deonjang ( n = 45/118) 35 – 38 . Zearalenone mostly occurred in Deonjang samples ( n = 32/60) 35 ; ochratoxin A mainly in Meju ( n = 50/100) 37 , RYR from Malaysia ( n = 50/100) 33 and Deonjang (49/109) 33 – 35 ; deoxynivalenol in Soy sauce ( n = 38/40) 35 and Deonjang ( n = 12/60) 35 . RYR were the most vulnerable to citrinin contamination as the number of samples from Malaysia and China positive to citrinin were n = 50/50 and n = 43/114, respectively 33 , 34 , 39 .…”
Section: Contamination Sources In Fermented Foodsmentioning
confidence: 99%
“…Fermented foods such as doenjang are vulnerable to mycotoxin contamination because of the long duration of fermentation in the natural environment [15]. Mycotoxins, such as aflatoxins, are the most serious toxicants in fermented foods because of their potential toxicity to humans and animals [9,16,17]. Several studies have reported the presence of aflatoxins in different doenjang samples [15,18].…”
Section: Aflatoxin Analysis In Non-contaminated Doenjang During Ferme...mentioning
confidence: 99%
“…Occasionally, meju can be contaminated with aflatoxin-producing fungi such as Aspergillus flavus and Aspergillus parasiticus, leading to the contamination of doenjang with aflatoxins [7]. Aspergillus flavus produces aflatoxins B1 and B2, whereas A. parasiticus produces aflatoxins G1 and G2 [8,9]. Aflatoxin contamination poses a serious challenge to food safety, as it is associated with several health hazards.…”
Section: Introductionmentioning
confidence: 99%